ScaPD: a database for human scaffold proteins - Xiaomei Han; Jenny Wang; Jie Wang; Sheng Liu; Jianfei Hu; Heng Zhu; Jiang Qian (BMC Bioinformatics, 2017)
Abstract Background Scaffold proteins play a critical role in an increasing number of biological signaling processes, including simple tethering mechanism, regulating selectivity in pathways, shaping cellular behaviors. While many databases document the signaling pathways, few databases are devoted to the scaffold proteins that medicate signal transduction. Results Here, we have developed a user-friendly database, ScaPD, to describe computationally predicted, experimentally validated scaffold proteins and associated signaling pathways. It currently contains 273 scaffold proteins and 1118 associated signaling pathways. The database allows users to search, navigate and download the scaffold protein-mediated signaling networks. Conclusions Manually curated and predicted scaffold protein data will be a foundation for further investigation of the scaffold protein in the signal transduction. With maintained up-to-date data, ScaPD ( http://bioinfo.wilmer.jhu.edu/ScaPD ) will be a valuable resource for understanding how individual signaling pathways are regulated.